Weed Dynamics in Rice Fields : Influence of Soil Reaction and Fertility - Vidya A S (Department of Agronomy, College of Horticulture, 2003)
Weed control is the most expensive operation In nee culture in Kerala. An understanding of the association of different weeds and their adaptive mechanisms to different rice ecosystems in Kerala is essential for planning effective weed management practices. Therefore an investigation focusing on the influence of soil conditions and methods of rice growing, on the di.stribution, biology and ecology of weeds of rice in Kerala was carried out in the Department of Agronomy, College of Horticulture, K.A.U. during 2000-2002. Results of the Permanent Manurial Trial at RRS, Kayamkulam, revealed the dominance of Aeschynomene indica to low N , Scirpus juncoides to low P soils. The number of weed species was more in plots receiving all the fertilizers compared to those receiving no nutrients. The fungal, bacterial and actinomycete population was higher in plots supplied with nitrogen and phosphorus and or organic matter. The influence of soil conditions on weed flora was studied by conducting surveys across the various rice ecosystems. The data from the surveys were analyzed statistically and diversity indices such as Simpson's diversity index, Shannon's diversity index, Evenness index and the dissimilarity coefficient were worked out. Cluster analysis was also done and dendrograms were prepared grouping the different regions based on the similarity of weed flora. Striking dissimilarities were noticed in the distribution of grass weeds while it was lesser in the case of sedges, total weed flora and ferns and least in the case of broad leaf weeds. Kole, Pokkali, Kayal, Kari and Palakkad (Rabi season) regions showed much similarity in the flora of grass weeds, while there was 75 % dissimilarity for these regions to Chittur- and Karappadam lands. Investigations on the mechanisms of survival of some of the indicator weeds showed that Aeschynomene indica thrive in low N soils by fixing atmospheric N in its aerial nodules. Diplachne fusca adapt to the saline habitats by excreting the excess salt